INDIKATOR KEMANDIRIAN PEMBIAYAAN MADRASAH - Nanang Fattah (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractThe implementation of National Educational System Law (Undang Undang Sistem Pendidikan Nasional/UU Sisdiknas) needs a standardized educational quality, including the costing. Cost Independence Indicators for Madrasahs refer to Government Regulation (Peraturan Pemerintah/PP) No. 19 Year 2005, namely: (1) investment cost that consist of the provision of facilities and infrastructures, human resource development, and fixed working capital; (2) operating costs that include salary of the teachers and educational affairs staff, benefits, educational equipments, and also indirect educational operating costs as transportation, meal, etc; and (3) personal cost that comprise registration, tuition (SPP), books, stationary, etc. key indicators for evaluating cost independence of madrasahs can be seen from the ratio of government contribution to parent/ community contribution to the educational costing. The contribution of government to Islamic Elementary School (Madrasah Ibtidaiyah/MI), Islamic Junior High School (Madrasah Tsanawiyah/MTs) and Islamic Senior High School (Madrasah Aliyah/ MA) was 38%, 37% and 31% respectively; while contribution of the parent/community was 62%, 63% and 69% respectively. It means there was a disparity between the both ways of financing madrasahs with the role of community. In the future, it is recommended for government to keep the principle of equality and equivalency in giving their subsidy to madrasah